Elevated albumin-bilirubin score as a predictor of kidney stones in adults with type 2 diabetes mellitus: evidence from a cross-sectional study - Wenya Mo; Tao Zhou; Qifei Dong; Yuhan Chen; Xuechun Hu; Jun Xiao; Changming Wang; Ping Xiang (PeerJ)
The presence of kidney stones in individuals with type 2 diabetes mellitus (T2DM) poses a significant challenge and burden, yet the underlying pathogenesis remains elusive. This study aimed to reveal the relationship between the albumin-bilirubin (ALBI) score and kidney stones in adult patients with T2DM. This cross-sectional study was conducted using data from 9,511 eligible patients. The main outcome of interest was the incidence of kidney stones, with the ALBI score serving as the primary exposure factor. Logistic regression analysis was performed to calculate the odds ratios and 95% confidence intervals for the association between ALBI score and kidney stones. Our study found that a higher ALBI score was independently related to the presence of kidney stones in adult patients with T2DM. When the ALBI score was stratified into tertiles, compared to patients with an ALBI score in the T1 category, those with ALBI scores in the T2 and T3 categories exhibited a significantly higher prevalence of kidney stones after adjusting for multiple potential confounding factors. Additionally, our results revealed a non-linear relationship between ALBI score and the presence of kidney stones, which was further supported by subgroup and interaction analyses. These findings offer preliminary insights that could potentially inform future approaches to understanding kidney stone risk in adults with T2DM. Additional studies are needed to validate our conclusions.